1978
DOI: 10.1111/j.1570-7458.1978.tb02764.x
|View full text |Cite
|
Sign up to set email alerts
|

COPULATION, EGG PRODUCTION AND SEX‐RATIO IN PHYTOSEIULUS PERSIMILIS AND AMBLYSEIUS BIBENS (ACARI: PHYTOSEIIDAE)

Abstract: In Phytoseiulus persimilis Athias‐Henriot and Amblyseius bibens Blommers a relation was found between the duration of copulation and the resultant egg production. After 15 min of copulation no eggs were produced but after respectively 30, 60 and 90 min an increasing number of eggs were deposited. In P. persimilis the total number of eggs can be produced after one copulation of long duration but in A. bibens several copulations are necessary for total egg production. Evidence was found that egg deposition depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 7 publications
2
31
0
1
Order By: Relevance
“…A positive correlation between the mating duration and female oviposition has been reported in many phytoseiid species, such as Amblyseius andersoni (Chant) (Amano and Chant, 1978b), N. bibens (Blommers) (Schulten et al, 1978), Phytoseiulus persimilis (Athias-Henriot) (Amano and Chant, 1978b;Schulten et al, 1978), A. potentillae (Garman), Typhlodromus pyri (Scheuten) (Overmeer et al, 1982), N. barkeri (Hughes) (Momen, 1993), N. womersleyi (Schicha) (Tsunoda andAmano, 2001), andA. deleoni Muma andDenmark (Zaher et al, 2007).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…A positive correlation between the mating duration and female oviposition has been reported in many phytoseiid species, such as Amblyseius andersoni (Chant) (Amano and Chant, 1978b), N. bibens (Blommers) (Schulten et al, 1978), Phytoseiulus persimilis (Athias-Henriot) (Amano and Chant, 1978b;Schulten et al, 1978), A. potentillae (Garman), Typhlodromus pyri (Scheuten) (Overmeer et al, 1982), N. barkeri (Hughes) (Momen, 1993), N. womersleyi (Schicha) (Tsunoda andAmano, 2001), andA. deleoni Muma andDenmark (Zaher et al, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…The size of the spermatophore (or the mass of sperm and seminal fl uid) injected by each male was estimated by measuring the size of the infl ated vesicle of the female spermatheca using a micrometer attached to a phase-contrast microscope. A positive relationship has been demonstrated between spermatophore size and resultant total egg production (Amano and Chant, 1978b;Schulten et al, 1978).…”
Section: Interrupted Matingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterochromatinization in the part of the chromosomes was observed in eggs just after deposition (Nelson-Rees et al, 1980). Although cytological evidence is insufficient, this has been presented as pseudo-arrhenotoky: male-destined oocytes need to be fertilized to begin embryogenesis, and the heterochromatinization of the paternal genomes occurs in maledestined eggs, inducing the elimination of paternal genomes during embryogenesis, resulting in functionally haploid males (Schulten, 1985). This system was also described as "parahaploidy" in previous studies (e.g., Hoy, 1979) and was recently investigated as a form of "paternal genome loss" presented in several insects (Burt & Trivers, 2006).…”
Section: (A) (B)mentioning
confidence: 99%
“…However, Amano and Chant (1978) and Schulten et al (1978) showed that the amount of egg production is correlated with the amount of sperm accepted by females during copulation in Phytoseiulus persimilis, Amblyseius andersoni, and Amblyseius (= Neoseiulus) bibens. For instance, in a study of P. persimilis, in which copulation was artificially interrupted (Amano & Chant, 1978), the average number of eggs deposited gradually increased from 2.7 to 66.3 when the duration of copulation increased from 30 min to 130 min.…”
Section: Indirect Evidence For Insemination In Male Eggsmentioning
confidence: 99%